The training of the specialized physician within the European prospective - Manzoli, Francesco Antonio (Medicina e Morale, 1990)
The author deals with the training of the specialized physician in Italy, with reference to the opening of the European borders in 1993 which will allow the free movement of both patients and physicians and the creation of a single market for insurance companies. medicaments and biotechnology. The author refers to thc DPR 162/82 and concentratcs on the reorganization of the schools of specialization suggesting proposals in order to adapt to the European systems and particularly to technical-cultural updating.